Structure and Properties of clay nano-biocomposites based on poly(lactic acid) plasticized with polyadipates - Veronica, Martino (2010)
The use of nano-biocomposites based on plasticized poly(lactic acid) (PLA) has been proposed as a way to improve the polymer ductility and to expand PLA applications window. Novative nano-biocomposites were elaborated with PLA plasticized by polyadipates (15 wt%) with different molar masses (from 1500 to 2500 Da), with 2.1 wt% of an organo-modified montmorillonite (O-MMT). These materials showed enhanced ductility and barrier properties. The clay was swelled in liquid polyadipates prior to their blending with PLA to facilitate chains intercalation and nanofiller exfoliation during melt-blending. In certain processing conditions, quite homogenous and exfoliated structures were obtained, as shown by X-ray diffraction (XRD) and transmission electronic microscopy (TEM) results. Irrespective of the average molar mass of the polyadipate, the clay addition induced a reduction in around 25% in oxygen transmission rate (OTR) without an important detriment in tensile properties. Nano-biocomposites prepared with higher molar masses polyadipates showed the highest thermal stability as well as the lowest OTR, resulting in very promising and novative materials for different applications such as soft packaging.